The Fracture Characteristic of Three Collinear Cracks under True Triaxial Compression - Jianjun Liu; Zheming Zhu; Bo Wang (The Scientific World Journal)
The mechanical behavior of multicracks under compression has become a very important project in the field of fracture mechanics and rock mechanics. In this paper, experimental and numerical studies on the fracture property of three collinear cracks under compression were implemented. The specimens were a square concrete plate, and the cracks were made by a very thin film. The tests were conducted by using true triaxial loading device. In the numerical study, the Abaqus code was employed. The effect of crack orientation and the confining stress on cracked specimen compressive strength were investigated. The results show that the critical stresses of cracked specimens change with crack inclination angles, and, as the angle is 45°, the critical stress is the lowest; the critical stresses increase with the confining stresses.